Data analysis, classification and the forward search : proceedings of the Meeting of the Classification and Data Analysis Group (CLADAG) of the Italian Statistical Society, University of Parma, June 6-8, 2005 - Classification Group of SIS. Meeting (2005; Zani, Sergio (Berlin : Springer, 2006)
41